Temporary and Permanent Viscosity Loss Correlated to Hydraulic System Performance. Issue 5 (3rd September 2018) - Michael, Paul; Cheekolu, Mercy; Panwar, Pawan; Devlin, Mark; Davidson, Rob; Johnson, Duval; Martini, Ashlie
ABSTRACT: Straight- and multigrade fluids were evaluated in a hydraulic dynamometer that incorporated a pressure-compensated axial piston pump and a fixed displacement axial piston motor. Pump, motor, pressure compensator, and directional control valve internal flow losses were determined under various conditions of pressure, speed, and temperature. Fluid samples were collected before and at various times during the dynamometer experiments, and viscosity measurements were performed to probe for correlations between viscosity, operating time, and system leakage flow losses. The low shear rate viscosities of the multigrade fluids decreased linearly throughout the duration of testing due to polymer degradation. However, system flow losses did not exhibit a statistically significant increase as the multigrade fluids sheared down. The fluids were also characterized by their permanent viscosity loss produced in sonic shear and tapered bearing tests and by their temporary shear thinning measured in an ultra-high-shear viscometer at several temperatures. The effects of these viscous properties were analyzed using an empirical model to identify which measures of viscosity were most correlated with flow loss. The results suggested that the relative contributions of temporary and permanent viscosity loss change as the fluid is used. Further, analysis of torque loss and input power revealed that input power and losses are more useful indicators of the effect of fluids on hydraulic system performance than pump efficiency.